Contribution to phytocoenology and ecological relations of ragweed (Ambrosia artemisiiflia L.) in Canton Sarajevo - Hasanbegovic, Anis; Murtic, Senad; Basic, Fejzo (Acta herbologica, 2024)
Ragweed is neophyte which inhabits various cultures and ruderal habitats. That is reason why this paper is dedicated to phytocoenology and ecological relations of ragweed in a such habitat. The research was carried out in the area of former railway freight and custom terminal, in period from 2021 to 2023. Phytocoenological image was made and all the parameters were done: life form, phytocoenological affiliation, floral elements, indicator values and soil analysis. The aim of the paper is to present the places where ragweed occurs, as well as under what ecological conditions and with what other species.This research yielded new data on the phytocoenology of ragweed, determined in the vegetation of the order Chenopodietalia. A total of 69 species from 23 families were indentified in the vegetation. The most numerous of Asteraceae family. Phytocoenologically, the largest number of species belongs to the order Chenopodietalia, and as far as the indicator values are concerned, the most numerous are representatives of tertiary vegetation.Hemicryptophytes predominate in life forms, and concerning the floral elements, 40 different elements from 9 groups were noted. The most numeros group is Eurasian, and the most numerous individal floral elements are euras-smed and eurassubozean-smed.
Keywords: phytocoenology; hemicriptophytes; ragweed; association; Chenopodietalia; weed